SAFETY AND HEALTH ANALISYS IMPLEMENTATION OF CONSTRUCTION PROJECTS WORK SAFETY IN STUDY ACEH PROVINCY - Yasir Amani (Universitas Malikussaleh, 2019)
Material losses suffered by the company due to the applied program and appropriate safety management among other things, cessation of work which resulted in reduced production and increased frequency of repair or rehabilitation equipment/supplies. The purpose of this study was to assess the level of understanding, awareness, and the factors and constraints of the implementation of safety management programs work by the company to the contractor. To achieve this end, it is the goal of research is to identify the level of understanding and awareness of the parties to the contractor (contractor) on safety at construction project sites, identify the factors and constraints of the implementation of safety management program at the project site construction work, and to identify risks to safety that occurred construction project location. The research data obtained through a questionnaire about the respondent's profile and project descriptions, safety program implementation checklists, and questionnaires Perceptions of contractor safety programs. The results show a variable level of understanding and awareness of the parties to the contractor (contractor) on safety at construction project sites, the most dominant subvariabel selected respondents is subvariabel